The quasi-cooling effect of relativistic charged particles beams - Kulish, V.V.; Gubanov, I.V.; Nguen Ai Vent; Brusnik, A.J. (Вопросы атомной науки и техники, 2007)
A possibility of realization of a new, of principle, physical phenomenon is shown. This is the phenomenon of energy equalization of charged particle beams in the time their acceleration in the crossed undulative electric and magnetic fields (EH-fields). The phenomenon predicted is referred to as the quasi-cooling effect. Main properties and features of the effect are studied. In particular, it is shown that it would be experimentally observed for the existing today level of acceleration technologies. Описано новий фізичний ефект - ефект вирівнювання енергій заряджених частинок пучка під час їх прискорення в схрещених електричному та магнітному ондуляторних полях (EH-полях). Даний ефект трактується як ефект ефективного охолодження. Вивчено загальні властивості та основні характеристики даного ефекту. Зокрема показано, що дане явище може бути експериментально реалізовано на існуючому рівні прискорювальних технологій. Описан новый физический эффект - эффект выравнивания энергий заряженных частиц пучка при их ускорении в скрещенных электрическом и магнитном ондуляторных полях (EH-полях). Данный эффект трактуется, как эффект эффективного охлаждения. Изучены основные особенности и характеристики данного эффекта. В том числе показано, что данный эффект может быть экспериментально реализован на существующем уровне ускорительных технологий.